Polyethylenimine-coated SPIONs trigger macrophage activation through TLR-4 signaling and ROS production and modulate podosome dynamics. (June 2015) - Mulens-Arias, Vladimir; Rojas, José M.; Pérez-Yagüe, Sonia; Morales, María P.; Barber, Domingo F.
Abstract: Polyethylenimine (PEI) is widely used as transfection agent in preclinical studies, both in vitro and in vivo. Due to their unique chemical and physical properties, SPIONs (superparamagnetic iron oxide nanoparticles) have been thoroughly studied as nanocarriers. PEI appears to activate different immune cells to an inflammatory response (M1/TH 1), whereas the SPION-induced response seems to be context-dependent; the immunogenicity of the combination of these components has not been studied. Here we show that PEI-coated SPIONs (PMag) activate macrophages, as determined by measuring IL-12 secretion into culture medium and upregulation of several genes linked to the M1 phenotype. PMag-induced phosphorylation of p38 MAPK, p44/p42 MAPK and JNK, and upregulation of CD40, CD80, CD86 and I-A/I-E activation markers. PMag-induced macrophage activation depended partially on TLR4 (Toll-like receptor 4) and ROS (reactive oxygen species) signaling. Comparison of these responses with the LPS (lipopolysaccharide)-induced phenotype showed differences in gene expression profiling. PMag positively modulated podosome formation in murine macrophages, but hampered gelatin degradation by these cells. In conclusion, PMag induced an M1-like phenotype that was partially dependent on both TLR4 and ROS. These results show the adjuvant potential of PMag and suggest their use in vaccination schedules.